2014
DOI: 10.1111/poms.12110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Trade‐offs among Multiple Objectives for Humanitarian Aid Delivery Using Expert Preferences

Abstract: H umanitarian aid agencies deliver emergency supplies and services to people affected by disasters. Scholars and practitioners have developed modeling approaches to support aid delivery planning, but they have used objective functions with little validation as to the trade-offs among the multiple goals of aid delivery. We develop a method to value the performance of aid delivery plans based on expert preferences over five key attributes: the amount of cargo delivered, the prioritization of aid by commodity typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 30 publications
3
130
1
1
Order By: Relevance
“…Survey as a well known research instrument, is applied in various disciplines to collect data for obtaining understanding and generalising insights (e.g., Yang, 2012;Pentina et al 2013;Abareshia and Mollaa, 2013;Lee et al, 2011;Kwok, 1995;Shim et al, 2007;van der Vaart and van Donk, 2008;Gralla et al, 2013). Within this research, the survey samples were members of Chinese medical supply chains, including manufacturers, wholesalers, retailers, hospitals and other healthcare service providers with e-commerce system applied in their business operations.…”
Section: Focus Group and Surveymentioning
confidence: 99%
“…Survey as a well known research instrument, is applied in various disciplines to collect data for obtaining understanding and generalising insights (e.g., Yang, 2012;Pentina et al 2013;Abareshia and Mollaa, 2013;Lee et al, 2011;Kwok, 1995;Shim et al, 2007;van der Vaart and van Donk, 2008;Gralla et al, 2013). Within this research, the survey samples were members of Chinese medical supply chains, including manufacturers, wholesalers, retailers, hospitals and other healthcare service providers with e-commerce system applied in their business operations.…”
Section: Focus Group and Surveymentioning
confidence: 99%
“…According Gralla et al [1], equity refers to fairness in distribution of services among recipients, and thus the optimal criteria concerned with equity include the latest arrival time, the sum of arrival times, and the smallest demand satisfaction rate. Gutjahr and Nolz [2] refined the scheme of Gralla et al [1] by partitioning the group "effectiveness" into the subgroups of response time, travel distance, coverage, reliability, and security and created seven groups of optimization criteria: (1) cost, including fixed cost for the procurement of equipment, supply-side travelling cost, facility-related cost, and the costs incurred for human resources; (2) response time, such as latest arrival time and average arrival time; (3) travel distance; (4) coverage, which measures the degree to which necessary services are provided to satisfy the demands; (5) reliability, which measures the probability of being able to steadily succeed with reference to other certain criteria, such as coverage or response time, in view of an uncertain environment; (6) security, which measures operation risks; (7) equity, normally measured by considering the worst-case value of a measure of disutility, such as the latest arrival time or smallest demand satisfaction rate as proposed by Gralla et al [1]; (8) distress, subsumed by Gutjahr and Nolz [2] in psychological or social costs. Furthermore, it is observed that sustainable development has become widely spread in recent years and more and more researchers focus their studies on sustainable operations by taking into consideration the factors of system's sustainability [3].…”
Section: Optimization Criteriamentioning
confidence: 99%
“…The purpose of this section is not to perform an exhaustive overview of the literature but to reveal the following: (1) How the optimization models are constructed? (2) What kind of methods have been developed for solving such models efficiently and effectively?…”
Section: Scientific Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such optimization approaches assume objectives of relief distribution are known, as well as their relative importance when more than one objective is considered. Some authors have also attempted to assess trade-offs among humanitarian criteria [8], while others have focused on the development of performance measurements suitable for the field [4,9,10]. Yet, the problem-structuring phase has been given little attention by modelers, even though it is argued to be a crucial step for developing better alternatives to solve a problem [11,12].…”
Section: Introductionmentioning
confidence: 99%